A highly durable carbon-nanofiber-supported Pt–C core–shell cathode catalyst for ultra-low Pt loading proton exchange membrane fuel cells: facile carbon encapsulation. Issue 9 (31st July 2019) - Karuppannan, Mohanraju; Kim, Youngkwang; Gok, Sujin; Lee, Eunjik; Hwang, Jee Youn; Jang, Ji-Hoon; Cho, Yong-Hun; Lim, Taeho; Sung, Yung-Eun; Kwon, Oh Joong
Abstract : Ultra-stable Pt cathode catalysts in ultra-low Pt loading proton exchange membrane fuel cells were synthesized by facile carbon encapsulation. Abstract : The carbon encapsulation of nanosized Pt cathode catalysts for ultra-low Pt loading proton exchange membrane fuel cells is an effective approach to enhance their stability and catalytic activity for the oxygen reduction reaction (ORR). However, the synthesis procedures for such a catalyst are delicate and cumbersome. Therefore, it is difficult to use such procedures for mass production. Here, we have developed a facile strategy for synthesizing carbon-encapsulated Pt nanoparticles supported on carbon nanofibers (CNFs) using a Pt–aniline complex. This strategy begins with applying a wet Pt–aniline complex coating to CNFs. Heat-treating the coated CNFs produced 3–4 nm-sized Pt nanoparticles that were uniformly coated with a layer of carbon on the CNF surface (Pt@CS/CNF). Compared to other carbon-coated Pt catalysts, the stability and catalytic activity of Pt@CS/CNF for the ORR are high owing to the robustness of the carbon shells that secure the Pt nanoparticles. In a unit cell test, the performance of Pt@CS/CNF heat-treated at 900 °C was almost maintained for 30 000 accelerated stability test cycles, showing a negligible voltage loss at an operating current density of 0.8 A cm −2 .